2019
DOI: 10.1155/2019/1248342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Genital Nerve Stimulation Amplitude on Bladder Capacity in Spinal Cord Injured Subjects

Abstract: Background/Purpose. Few studies have investigated the effects of changing the amplitude of dorsal genital nerve stimulation (GNS) on the inhibition of neurogenic detrusor overactivity in individuals with spinal cord injury (SCI). The present study determined the acute effects of changes in GNS amplitude on bladder capacity gain in individuals with SCI and neurogenic detrusor overactivity. Methods. Cystometry was used to assess the effects of continuous GNS on bladder capacity during bladder filling. The cystom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…All of the studies measured changes after a range of 2-12 weeks of treatment. Several studies were excluded due to results contaminated with non-SCI participants (25-27) and without the control group (6,(28)(29)(30)(31). Besides, one study did not provide spinal injury details, for example, the level, completeness, and SCI phase (32).…”
Section: Search Resultsmentioning
confidence: 99%
“…All of the studies measured changes after a range of 2-12 weeks of treatment. Several studies were excluded due to results contaminated with non-SCI participants (25-27) and without the control group (6,(28)(29)(30)(31). Besides, one study did not provide spinal injury details, for example, the level, completeness, and SCI phase (32).…”
Section: Search Resultsmentioning
confidence: 99%
“…McCrery et al [34] reported that sacral neuromodulation was a safe and effective approach to improve urinary urgency incontinence symptoms in a majority of patients with urinary dysfunction and fecal incontinence, when conservative treatlents failed. Yeh et al [35] reported a linear correlation between the amplitude of dorsal genital nerve stimulation (GNS) ranging from 1 to 4 times the threshold and bladder capacity gain stimulation in acute SCI patients with neurogenic detrusor overactivity. Bourbeau et al [36] also found that short term at home GNS could reduce urinary incontinence and help subjects to achieve adequate bladder control.…”
Section: Neurostimulation/neuromodulation and The Brain-computer Interface (Bci)mentioning
confidence: 99%
“…We recommend that patients experience the device first on their arm, and the identified moderate currents are expected to be used in urinary applications. For effective bladder inhibition with wireless-GEN, a moderate stimulation current needs to be used [12,13,15,16]. This current can be ascertained by palpating the anus and identifying moderate anal reflex contractions.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle is a proxy for sensory nerve activation that mediates neuromodulation because only motor responses are easily measured. For effective bladder inhibition with wireless-GEN, a moderate stimulation current needs to be used [12,13,15,16]. This current can be ascertained by palpating the anus and identifying moderate anal reflex contractions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation